Methods, Implementation, and Application of Cyber Security Intelligence and Analytics - Jena, Om Prakash; Gururaj, H. L., 1988-; Pooja, M. R., 1982-; Kumar, S. P. Pavan, 1989- (Hershey, PA : Information Science Reference, an imprint of IGI Global, 2022)
"This book looks at the intersection of Artificial Intelligence and Cyber security which has emerged as one of the most promising use cases for the advancement of Cyber security in the technological age"--
Includes bibliographical references (pages 241-260) and index.
Keywords: Computer networks -- Security measures -- Data processing; Artificial intelligence